All-dielectric nonlinear metasurface: from visible to vacuum ultraviolet - Zhihui Wang; Rong Lin; Jin Yao; Din Ping Tsai (npj Nanophotonics)
Abstract All-dielectric nonlinear metasurfaces have higher damage thresholds and more flexible manipulation of resonant modes. Because of the intrinsic advantages of short-wavelength regions, related research gradually moved from the visible to the vacuum ultraviolet (VUV) region. This review introduces the theoretical framework: resonant modes enhance the local electromagnetic field and promote nonlinear polarization. After analyzing nonlinear efficiency enhancement mechanisms, we explore nonlinear modulation strategies. Finally, potential research directions are discussed.